2017
DOI: 10.1111/psyp.12858
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal oxygenation and the acoustic startle eyeblink response during exercise: A test of the dual‐mode model

Abstract: The interplay between the prefrontal cortex and amygdala is proposed to explain the regulation of affective responses (pleasure/displeasure) during exercise as outlined in the dual-mode model. However, due to methodological limitations the dual-mode model has not been fully tested. In this study, prefrontal oxygenation (using near-infrared spectroscopy) and amygdala activity (reflected by eyeblink amplitude using acoustic startle methodology) were recorded during exercise standardized to metabolic processes: 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…The aforementioned evidence has demonstrated that physical exercise could exert influences on the functions of both amygdala and OFC. The dual-mode theory postulates that affective responses to exercise are determined by the continuous interplay between cognitive parameters (from PFC to the amygdala) and interoceptive cues (from subcortical homeostatic afferents to amygdala) [ 20 ]. A greater ability to down-regulate negative emotions means a greater amygdala attenuation and greater inverse OFC/dlPFC-amygdala FC [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The aforementioned evidence has demonstrated that physical exercise could exert influences on the functions of both amygdala and OFC. The dual-mode theory postulates that affective responses to exercise are determined by the continuous interplay between cognitive parameters (from PFC to the amygdala) and interoceptive cues (from subcortical homeostatic afferents to amygdala) [ 20 ]. A greater ability to down-regulate negative emotions means a greater amygdala attenuation and greater inverse OFC/dlPFC-amygdala FC [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lateral OFC activity was associated with down-regulation of emotional responses, and a functional coupling of the amygdala during the negative appraisal process [ 42 ]. The prefrontal control system influences the amygdala activity in the emotional system [ 43 ] by combating the sensory input to the amygdala [ 20 ] and then affect the emotional response. On the other hand, exercise could directly decrease the activity of amygdala.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Individual differences in physical (e.g., physical activity level [39]), psychological status (e.g., exercise preference and tolerance of intensity) [40,41], and macronutrient intake (e.g., low-carbohydrate diets) [42] also account for the discrepancy. From the aspect of the neural system, the interplay of prefrontal cortex and amygdala have been revealed to regulate affective responses during exercise [43][44][45]. For example, individual differences in the ability to maintain prefrontal cortex involvement, indicated by self-reported tolerance, are possibly associated with feelings of pleasure or displeasure [41,44].…”
Section: Discussionmentioning
confidence: 99%